Refinement of some inequalities for means - Mira-Cristiana Anisiu; Valeriu Anisiu (Journal of Numerical Analysis and Approximation Theory, 2006)
We consider weighted arithmetic means as, for example, \(α G+(1-α)C,\) with \(α\in(0,1)\), \(G\) \(C\) being the geometric and anti-harmonic means, and we find the range of values of \(α\) for which the weighted mean is still greater or less than some suitable means, in this case the arithmetic and Hölder ones.